The Optimization of Capital Structure in Maximizing Profit and Corporate Value - Effendi, Kharisya Ayu (Binus Business Review, 2017)
The purpose of this research was to determine the optimal capital structure which could maximize profits and corporate value. The used method was quantitative descriptive analysis. Moreover, the data used was secondary data in the Jakarta Islamic Index (JII) from 2011 to 2015. The results of this research show that companies which have optimal capital structure are in line with the trade-off theory models. The capital structure is optimal if the debt levels are to a certain extent so that the corporate value will increase. However, if the debt limit passes the certain degree, profit and corporate value will decrease. Meanwhile, pecking order theory in this research does not conform and cannot be said to be optimal because of the low debt level describing the opposite result with the theory as low profits.